2016
DOI: 10.18632/oncotarget.9594
|View full text |Cite
|
Sign up to set email alerts
|

The molecular mechanism of G2/M cell cycle arrest induced by AFB1 in the jejunum

Abstract: Aflatoxin B1 (AFB1) has potent hepatotoxic, carcinogenic, genotoxic, immunotoxic and other adverse effects in human and animals. The aim of this study was to investigate the molecular mechanism of G2/M cell cycle arrest induced by AFB1 in the jejunum of broilers. Broilers, as experimental animals, were fed 0.6 mg/kg AFB1 diet for 3 weeks. Our results showed that AFB1 reduced the jejunal villus height, villus height/crypt ratio and caused G2/M cell cycle arrest. The G2/M cell cycle was accompanied by the increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 48 publications
4
24
1
Order By: Relevance
“…However, it is interesting to find that under light microscope, no shedding of the absorptive cells in the villi of cecal tonsils was observed in the AFB 1 group, which is consistent with Ledoux's report in the small intestine, when male broilers were exposed to 4 mg /kg AFB 1 for 3 weeks [ 26 ]. However, this result is different from early researches in the jejunum in which the shedding of the absorptive cells occurred on the apical region of villi in the broilers exposure to 0.3 or 0.6 mg/kg AFB 1 [ 27 , 28 ]. This discrepancy may be related to the different segments of gastrointestinal tract or AFB 1 concentration.…”
Section: Discussioncontrasting
confidence: 94%
“…However, it is interesting to find that under light microscope, no shedding of the absorptive cells in the villi of cecal tonsils was observed in the AFB 1 group, which is consistent with Ledoux's report in the small intestine, when male broilers were exposed to 4 mg /kg AFB 1 for 3 weeks [ 26 ]. However, this result is different from early researches in the jejunum in which the shedding of the absorptive cells occurred on the apical region of villi in the broilers exposure to 0.3 or 0.6 mg/kg AFB 1 [ 27 , 28 ]. This discrepancy may be related to the different segments of gastrointestinal tract or AFB 1 concentration.…”
Section: Discussioncontrasting
confidence: 94%
“…These findings were recently corroborated by feeding broiler chicken with feed containing 0.6 mg AFB1/kg for up to 21 days and monitoring structural and functional changes in the small intestine [128]. The study showed various structural and histopathological injuries similar to those described above regarding the increased depth of villi with decreased height and area [127], in addition to other histopathological alterations in the small intestine, including mitochondrial vacuolation and loss of cristae, reduced numbers of the absorptive cell goblets and the junctional complexes. Such changes dramatically alter the barrier function of the intestine to interfere not only with nutrient absorption, but also with the innate immune response as a protective means against the invasion of pathogens or toxins.…”
Section: Innate Immunitysupporting
confidence: 63%
“…Aflatoxins have also been demonstrated to disrupt the integrity and function of the mechanical barrier of intestines by interfering with the cell cycle progression or by destroying the intestinal epithelial cells and the tight junctions (TJs) that cement them together. Administration of 0.6 mg AFB1/kg diet to broilers for 3 weeks stalled the cell cycle at the G2/M phase causing a reduction in the height jejunum and in the ratio of villus height/crypt, thereby impairing their function as a selective barrier [127]. These findings were recently corroborated by feeding broiler chicken with feed containing 0.6 mg AFB1/kg for up to 21 days and monitoring structural and functional changes in the small intestine [128].…”
Section: Innate Immunitymentioning
confidence: 85%
“…MYC proto-oncogene is reported as an oncogenic transcription factor, promotion of the cell cycle is the major oncogenic mechanism [22], and it has been reported that N-Myc (one of the MYC family) differentially regulating miR-421/ATM pathway contributes to ADT and enzalutamide resistance [23]. The "G2M checkpoint" and "MITOTIC spindle" are gene sets involved in cell cycle [24,25]. These results indicate that TUBB4A and CSRP2 may participate in docetaxel resistance by E2F transcription factor and MYC protooncogene in the process of cell cycle.…”
Section: Discussionmentioning
confidence: 99%